2022
DOI: 10.3390/app12147076
|View full text |Cite
|
Sign up to set email alerts
|

Positioning Information Based High-Speed Communications with Multiple RISs: Doppler Mitigation and Hardware Impairments

Abstract: In this paper, we consider a multiple reconfigurable intelligent surface (RIS)-assisted system using positioning information (PI) to explore the potential of Doppler effect mitigation and spectral efficiency (SE) enhancement in high-speed communications (HSC) in the presence of hardware impairments (HWI). In particular, we first present a general multi-RIS-assisted system model for HSC with HWI. Then, based on PI, different phase shift optimization strategies are designed and compared for maximizing SE, elimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(126 reference statements)
0
0
0
Order By: Relevance
“…Considering the optimal phase shift φ opt mn (t) in ( 23), recall the DS f 0 (t) in (3) and f mn (t) in (12), and note that d(ζ mn (t))/dt = 0, we have…”
Section: Doppler Shift Alignmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the optimal phase shift φ opt mn (t) in ( 23), recall the DS f 0 (t) in (3) and f mn (t) in (12), and note that d(ζ mn (t))/dt = 0, we have…”
Section: Doppler Shift Alignmentmentioning
confidence: 99%
“…Interestingly, they showed that the HWI enlarges the delay spread of the HSC, but not the ability to mitigate Doppler effects. Moreover, the authors of [12] showed that due to the HWI, a multiple RIS system suffers from a wider delay spread as well as significant degradation of the SE. However, the channel models considered in [10][11][12] did not take into account the non-light-of-sight (NLoS), i.e., the Rayleigh component.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations